KEPEMIMPINAN TRANSFORMASIONAL UNTUK SEKOLAH MASA DEPAN: STRATEGI MENINGKATKAN KINERJA GURU MENUJU INDONESIA EMAS 2045 - Yuyun Tobondo (Yayasan Sukma, 2025)
This study addresses the question of how transformational leadership enhances teacher performance in shaping the future school toward the vision of Indonesia Emas 2045. Positioned as a literature review, the research views transformational leadership not merely as a managerial style, but as a long-term strategy grounded in values, motivation, and organizational commitment. The discussion explores the dimensions of transformational leadership and their implications for intrinsic motivation, school culture, and continuous professional development. The findings reveal that transformational leadership generates systemic effects at the individual, team, and organizational levels, fostering an educational ecosystem that is adaptive, innovative, and sustainable. Thus, transformational leadership emerges as a strategic foundation for preparing future schools that are visionary, inclusive, and globally competitive.